Species delimitation and phylogenetic relationships in a genus of African weakly-electric fishes (Osteoglossiformes, Mormyridae, Campylomormyrus) - Lamanna, Francesco; Kirschbaum, Frank; Ernst, Anja R. R.; Feulner, Philine G. D.; Mamonekene, Victor; Paul, Christiane; Tiedemann, Ralph (Molecular phylogenetics and evolution, 2016)
African weakly-electric fishes (Mormyridae) are able to communicate through species-specific electric signals; this feature might have favoured the evolutionary radiation observed in this family (over 200 species) by acting as an effective pre-zygotic isolation mechanism. In the present study we used mitochondrial (cytb) and nuclear (rps7, scn4aa) markers in order to reconstruct a species-phylogeny and identify species boundaries for the genus Campylomormyrus, by applying inference methods based on the multispecies coalescent model. Additionally, we employed 16 microsatellite markers, landmark-based morphometric measurements, and electro-physiological analyses as independent lines of evidence to the results obtained from the sequence data. The results show that groups that are morphologically different are also significantly divergent at the genetic level, whereas morphologically similar groups, displaying dissimilar electric signals, do not show enough genetic diversity to be considered separate species. Furthermore, the data confirm the presence of a yet undescribed species within the genus Campylomormyrus.